2011
DOI: 10.7745/kjssf.2011.44.4.637
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects of Arbuscular Mycorrhizal Fungi and Plant Growth Promoting Rhizobacteria for Sustainable Agricultural Production

Abstract: Soil microorganisms play a major role in improving soil fertility and plant health. Symbiotic arbuscular mycorrhizal fungi (AMF) form a key component of the soil microbial populations. AMF form a mutualistic association with the host plant and exert a positive influence on its growth and nutrient uptake. The establishment of mycorrhizal symbioses with the host plant can positively be influenced by plant growth promoting rhizobacteria through various mechanisms such as increased spore germination and hyphal per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 101 publications
(89 reference statements)
0
13
0
1
Order By: Relevance
“…These microorganisms increased the foliar uptake of phosphorus levels in Trifolium repens (white clover) plants, which stimulated the production of biomass and mycorrhizal colonization compared with the inoculation of each individual organism. According to Ramasamy et al (2011), plant growth-promoting rhizobacteria, such as actinomycetes, could positively influence the development of mycorrhizal symbiosis through different mechanisms of action. In this regard, Carpenter-Boggs et al (1995) found 19 actinomycetes capable of stimulating in vitro germination of G. margarita by producing volatile compounds that could benefit the plant in terms of greater growth.…”
Section: Plant Growth Promotion By Amf and Actinomycetesmentioning
confidence: 99%
“…These microorganisms increased the foliar uptake of phosphorus levels in Trifolium repens (white clover) plants, which stimulated the production of biomass and mycorrhizal colonization compared with the inoculation of each individual organism. According to Ramasamy et al (2011), plant growth-promoting rhizobacteria, such as actinomycetes, could positively influence the development of mycorrhizal symbiosis through different mechanisms of action. In this regard, Carpenter-Boggs et al (1995) found 19 actinomycetes capable of stimulating in vitro germination of G. margarita by producing volatile compounds that could benefit the plant in terms of greater growth.…”
Section: Plant Growth Promotion By Amf and Actinomycetesmentioning
confidence: 99%
“…While mycorrhizae transport phosphorus throughout the soil, it may not be available to the host plant without the P-solubilizing activity of certain rhizobacteria; thus, both symbionts play important roles. Fungi may facilitate colonization of the host by rhizobia and fluorescent pseudomonads (Bianciotto et al 1996), and some bacteria may improve spore colonization in turn (Ramasamy et al 2011). In addition, VAM improve rhizobial nodulation and nitrogen fixation (Table 2).…”
Section: Vesicular-arbuscular Mycorrhizae (Vam)mentioning
confidence: 99%
“…Phosphorus-solubilizing bacteria, including representatives of Rhizobium, Pseudomonas, Bacillus, and Burkholderia, increase the availability of soil P to the host plant (Barka et al 2006;Hayat et al 2010;Ramasamy et al 2011). This is often achieved by releasing organic acids, such as the 2-ketoglutonic acid produced by Rhizobium meliloti, to dissolve mineral phosphates (Halder and Chakrabartty 1993;Hayat et al 2010).…”
Section: Improved Plant Nutritionmentioning
confidence: 99%
See 2 more Smart Citations